The mall ebook A novel. - McCafferty, Megan (2020)
New York Times bestselling author Megan McCafferty returns to her roots with this YA coming of age story set in a New Jersey mall. The year is 1991. Scrunchies, mixtapes and 90210 are, like, totally fresh. Cassie Worthy is psyched to spend the summer after graduation working at the Parkway Center Mall. In six weeks, she and her boyfriend head off to college in NYC to fulfill The Plan: higher education and happily ever after. But you know what they say about the best laid plans... Set entirely in a classic "monument to consumerism," the novel follows Cassie as she finds friendship, love, and ultimately herself, in the most unexpected of places. Megan McCafferty, beloved New York Times bestselling author of the Jessica Darling series, takes readers on an epic trip back in time to The Mall .